Nuclear power worldwide: Development plans in newcomer countries negligible - Lars Sorge; Claudia Kemfert; Christian R. von Hirschhausen; Ben Wealer (DIW Weekly Report, 2020)
At just 4.4 percent, the contribution made by nuclear power to meeting the world's primary energy requirements is marginal and on the decline. The current nuclear power fleet is outdated with around 200 plants due to be phased out over the next ten years compared to as few as 46 new nuclear power plants under construction worldwide. Yet the nuclear industry, particularly the World Nuclear Association (WNA), is propagating the narrative that there is a plethora of countries interested in constructing their first nuclear plants. The reality is quite different, however. As few as four countries are in the process of building their first nuclear power plants and even these projects are heavily subsidized and experiencing significantly delays. As for other potential newcomers, their plans are, at best, vague, frequently abandoned, or delayed. Given the absence of economic and financial incentive, DIW Berlin has conducted an empirical analysis of other characteristics in potential newcomer countries. Our findings show that these countries tend to have a lack of democratic freedom, something which generally goes hand-in-hand with centralized power structures and weak opposition. Moreover, our analysis suggests that countries exporting nuclear technology more often than not pursue geopolitical objectives, something that currently applies to Russia, in particular. Within international organizations, especially the International Atomic Energy Agency (IAEA) but also Euratom, Germany should be working toward ensuring that countries are not encouraged to construct their first nuclear power plants, that the necessary safety standards are met where nuclear power plants are already built or are in operation, and that as yet unresolved issues relating to decommissioning and the long-term storage of nuclear waste worldwide are addressed.
Keywords: L95; Q48; 330; nuclear power; geopolitics; investment; democracy